Does fertility respond to financial incentives? - Guy Laroque; Bernard Salanié (Center for Economic Studies and ifo Institute (CESifo), 2008)
There has been little empirical work evaluating the sensitivity of fertility to financial incentives at the household level. We put forward an identification strategy that relies on the fact that variation of wages induces variation in benefits and tax credits among comparable households. We implement this approach by estimating a discrete choice model of female participation and fertility, using individual data from the French Labor Force Survey and a fairly detailed representation of the French tax-benefit system. Our results suggest that financial incentives play a notable role in determining fertility decisions in France, both for the first and for the third child. As an example, an unconditional child benefit with a direct cost of 0.3% of GDP might raise total fertility by about 0.3 point.
Keywords: J13; J22; H53; 330; Population; fertility; incentives; benefits; Fruchtbarkeit; Familienpolitik; Ökonomischer Anreiz; Frankreich